Dimensional accuracy of vinyl polyether and polyvinyl siloxane impression materials in direct implant impression technique for multiple dental implants - Rohini Rajendran; N. Gopi Chander; Kuttae Vishwanathan Anitha; Muthukumar Balasubramanian (European Oral Research)
Purpose The present study compared the dimensional accuracy of vinyl polyether silicone (VPES) and polyvinyl siloxane (PVS) impression materials used for non-splinted (NS) and splinted (S) direct open-tray impression techniques for multiple implants inserted in simulated edentulous mandibles. Materials and Methods A mandibular stainless steel model with eight internal connections for implant analogs was fabricated to simulate a clinical scenario. The acrylic resin splinted and non-splinted direct impressions were obtained for both VPES and PVS materials. Seventy-two cast samples were divided into four groups based on the impression techniques and materials used. The dimensional accuracies of the casts were measured in three different axes using a computerized coordinate measuring machine (CMM), and were statistically compared. Results The differences in the distortion values between the VPES and PVS impression materials were not statistically significant. Similarly, the differences between the splinted and non-splinted groups among the VPES and PVS materials were not statistically significant. Conclusion The casts fabricated from VPS or PVS impression materials provide similar dimensional accuracy regardless of the implant splinting method.